STUDI KEMAMPUAN KEUANGAN DAERAH KABUPATEN POSO TAHUN 2010-2015 - Sanggona, Alfrianingsih (Katalogis, 2017)
This research aims to find out the development of local revenue and fiscal ability in its implicationÂ  on economic growth and express some views in running policy to improve economic growth. This was a qualitative reserarch with data analysis methode usig financial ability stipulated by Planing and National DevelopmentÂ  Board. Study of local revenue in Poso regency indicates that is has not meaningful development yet. Contribution of real of local revenue in Poso regency on state budget is still less, which is 5%. Local revenue still more influenced by central government that makes economic development run slowly. God cooperation from all party will surely give a great contribution for local revenue availability. The local revenue gained should be returned to society through infrastructure development which can be directly enjoyed by them. The research result reveals that ratio of local finance independency obtained the outcomes on the average of 3% or lies in instructive relation pattern. Fiscal decentralization degree ratio and routine ability index ratio show that local finance ability still lack, which is 5% and 6%. On suitability ratio, routine expenditure is higher than development expenditure with gap as much as 63%. Growth ratio, overall has negative growth becausethe improvement of local real revenue and local income total are not followed by development expenditure growth, but followed by routine expenditure growth. By seeing the analysis result, the local revenue development of Poso regency has not shown a meaningful development and local finance ability for the sake of local autonomy implementation that considered still lack.